PELATIHAN DASAR WEB MENGGUNAKAN FIGMA DALAM PEMBUATAN PORTOFOLIO UNTUK SISWA/I SMA SUMPAH PEMUDA - Andrian, Tio; Abdullah Muhajir; Iyu Priyatna (JAMAIKA: JURNAL ABDI MASYARAKAT, 2026)
The rapid development of digital technology requires senior high school students to possess digital literacy that is not only consumptive but also productive and applicable. One essential skill in this context is the ability to design a digital curriculum vitae as a professional self-representation medium that is informative and visually structured. This community service activity aimed to enhance the digital skills of students at SMA Sumpah Pemuda in designing digital curriculum vitae using Figma through practical digital training. The training method was implemented through hands-on activities, including an introduction to digital curriculum vitae concepts, information structuring, and independent visual design using Figma. The participants consisted of 27 twelfth-grade students from science and social studies streams. Data were collected through pretest and posttest assessments, practical evaluations, observations, and brief interviews. The results indicated a significant improvement in students’ understanding of digital curriculum vitae concepts and their ability to produce well-structured and visually appealing digital curriculum vitae suitable for professional use. In addition, the training contributed to increased student confidence and motivation in utilizing digital design technology productively. It can be concluded that digital curriculum vitae training using Figma is effective in improving digital literacy and design skills among senior high school students and can serve as a relevant model for community service programs supporting students’ readiness for higher education and the digital-based workforce. Keywords: digital curriculum vitae; Figma; digital literacy; digital training; senior high school students